Building Up Student Learning Outcomes Through Contextual Teaching and Learning (CTL) Learning Approaches in Discrete Mathematics Subjects in The Computer Engineering Study Program of The South Aceh Polytechnic - Fera Anugreni; Muhammad Anhar Pulungan (Jurnal Inotera, 2020)
Students graduating with a minimum score of C in the 2018/2019 even semester is 47%. Given the importance of the course objectives and the low learning outcomes achieved, a learning approach is applied which is expected to create active learning for students. To present active learning, the learning approach used must be familiar with students' daily lives. One learning approach that can emulate the daily lives of students is the Contextual Teaching and Learning (CTL) learning approach. The formulation of the problems in this study are a) is the application of CTL able to improve the learning outcomes of students in semester II of the Computer Engineering Study Program in Discrete Mathematics courses ?, b) how do lecturers manage learning with the CTL approach ?, and c) how are student learning activities using CTL? The purpose of this study was to a) determine the improvement of student learning outcomes, b) to determine the ability of lecturers to manage learning activities, and c) to determine student activities in learning. The research approach used in this research is quantitative and qualitative approaches, while the type of research is classroom action research (PTK). The subjects of this study were 16 students in the second semester of the Computer Engineering Study Program. The data collection techniques used in this study were a) test questions, and b) observation sheets. The study consisted of 2 (two) cycles, where the first cycle consisted of 3 meetings, while the second cycle consisted of 2 meetings. The results showed that the ability of lecturers to manage learning in cycles I and II was in a good category and the ability of lecturers to manage learning had increased when compared to cycle I to cycle II, from 3.88 to 4.06. Student learning activities in cycle II increased when compared to cycle I. The results of the first cycle test showed that 11 students completed, while in cycle II the results obtained 12 students completed. The percentage of student learning completeness during the first cycle to the second cycle was 68.75% and 75%. The increase in student learning completeness between cycle I and cycle II is 75% - 68.75% = 6.25%.